The socialization of students in the process of art activity in a mixed-age organization - Yu, Khomenko N. (TSNS "Interaktiv plus", LLC, 2018)
the article analyzes the experience of pedagogical research of students’ socialization in the process of their art activity in a mixed-age organization. It also provides the characteristic of some results, obtained in the research.